Students with Disabilities at Polish Universities - Garbat, Marcin; Paszkowicz, Maria Agnieszka (Studia Oeconomica Posnaniensia, 2015)
The paper presents the system of opportunities for supporting people with disabilities in the process of acquiring a university education. It also presents the impact of this support on the level of schooling according to the degree of disability, the profile of the university, the type of study and the region.